Producing and Concentrating Lenti-Cre for Mouse Infections - Gierut, Jessica J. (2014)
Lentiviral vectors offer versatility as vehicles for gene delivery. They can transduce a wide range of cell types and integrate into the host genome, which results in long-term expression of the transgene (Cre) both in vitro and in vivo. This protocol describes how lentiviral particles are produced, purified, and concentrated.